Head acceleration event exposure during elite men's and women's rugby union training - Hudson, S.; Tooby, J.; Roe, G.; Sawczuk, T.; Cazzola, D.; Cross, M.; Jones, B.; Kemp, S.; Whitehead, S.; Stokes, K. (Sports Medicine, 2026)
Objectives: The aim of this study was to describe the incidence and magnitude of head acceleration events (HAEs) during elite men`s and women`s rugby union training for different contact training levels and drill types. Method: Data were collected during the 2022-23 and 2023-24 seasons from 203 men and 125 women from 13 clubs using instrumented mouthguards (iMGs) during in-season training. One author reviewed the training videos to identify the contact level and drill type. HAE incidence was calculated per player minute. Results: For men`s forwards and backs, only 4.7% and 5.8% of HAEs were = 25 g and = 1.5 Krad/s2, and 3.4% and 4.4% for women`s forwards and backs, respectively. The incidence of = 5 g and = 0.4 Krad/s2 was highest during full-contact training for men`s forwards (0.20/min) and backs (0.16/min) and women`s forwards (0.10/min). HAE incidence was 2-3 times higher during repetition-based compared with game-based training drills for men`s forwards (0.25/min vs 0.09/min) and backs (0.22/min vs 0.09/min) and women`s forwards (0.09/min vs 0.04/min) and backs (0.08/min vs 0.03/min). HAE incidences were halved when repetition-based training drills used pads compared with no pads for men`s forwards (0.21/min vs 0.44/min) and backs (0.17/min vs 0.30/min), and women`s forwards (0.06/min vs 0.14/min) and backs (0.06/min vs 0.10/min). Conclusion: The average HAE incidence (~ 13-20% of weekly HAEs) and magnitude during an in-season training week is very low compared with matches. Opportunities to materially reduce HAE exposure in training are likely more limited than previously assumed. Future research on HAE load and injury, and understanding players` specific weekly training exposure, may inform effective individual player management.